The Extent of Practitioners' Involvement in the Delivery of Sustainable Urban Regeneration Projects in UK - Akotia, Julius; Opoku, Alex; Hafiz, Farahat (European Journal of Sustainable Development, 2017)
The requirement to deliver successful sustainable regeneration projects places enormous responsibility on the construction industry practitioners. While the concept of sustainable regeneration has being a big issue in the UK, and also being in operation within the construction industry over the years, it can be said that its achievement has been hampered and determined by numerous factors. One such factor which has affected and continues to affect and determine the sustainability outcome of regeneration projects, are the key practitioners who are tasked with the responsibility of delivering such regeneration projects. The findings of a study that obtained 193 responses through a questionnaire survey to explore the key practitioners’ levels of involvement in the delivery of sustainable regeneration projects in the UK is presented in this paper. The findings identified varied levels of practitioners’ involvement in the three main stages of the project delivery/development; early, construction and post construction. The findings revealed that clients’ representatives, commercial managers and architects were the most frequently involved practitioners during the early stages of the projects. The findings also indicated that practitioners who have sustainability assigned to their roles and their responsibilities, such as the regeneration managers, sustainability managers, training/corporate social responsibility managers were the least frequently involved in all the three delivery stages of the projects. Keywords: Sustainable regeneration, Key Practitioners, Level of involvement, Urban regeneration